A decade of village funds governance: evaluation, optimization, and institutional strengthening for sustainable rural development in Indonesia - Waworundeng, Welly; Monintja, Donald; Sampe, Stefanus; Santa, Nansi Margret (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
Village institutions are essential to the Village Fund governance. This study analyzes the factors contributing to the failure of these institutions in managing Village Funds and proposes strategies to enhance their capacity. The research was conducted in Warembungan Village and Kamangta Village in Minahasa Regency using a qualitative descriptive method. The findings indicate that the management of Village Funds is predominantly focused on short-term programs, such as Direct Cash Assistance. Key strategic policies related to this management include the Village Medium-Term Development Plan (VMTDP), Village Government Work Plan (VGWP), and Village Regulations regarding the Village Budget. Internal factors that hinder the efficiency of village institutions include the election of village heads not based on the majority, political interference, low transparency in recruitment processes, limited human resources, and inadequate welfare for officials. External factors include overlapping regulations, weak coordination among agencies, and ineffective supervision. As a result, budget efficiency is compromised, which increases the potential for mismanagement and conflicts of interest. To strengthen village institutions, it is essential to revise overlapping regulations, allow flexibility in the election of village heads, and enhance human resource capacity through competency-based selection. Furthermore, improving transparency in fund management, ensuring strict oversight from the government and community, and involving universities, media, and migrant communities are vital components for ensuring better village governance. With these strategies, village institutions are expected to support optimal and sustainable rural development.